Optimizing winged-bean meal through oven and autoclave heating as viable alternative for plant-based aquafeed - Tartila, Shobrina Silmi Qori; Mujtahidah, Tholibah; Azril, Muh.; Pramudita, Anjali Apta; Septiani, Lusi; Satria, Bagas Putra; Cristanto, Ignatius Abel; Oktavian, Muhammad Abizar Sakti; Risqulloh, Sultan Jibran; Astuti, Santika Dewi (Jurnal Ilmiah Pertanian, 2024)
Winged-bean meal can serve as a substitute for soybean meal in plant-based fish feed, despite its trypsin-inhibitor properties, which can be alleviated through heating processes. This study aimed to explore the potential of winged-bean meal subjected to different heating methods, namely oven (110 °C for 30 minutes) and autoclave (121 °C for 30 minutes), based on proximate analysis and trypsin activity. The study applied three treatments with four replications: oven heating (O), autoclave heating (A), and control (without heating, E). All data were analyzed using analysis of variance and Duncan’s multiple range test to determine the best treatment. Data were also compared to the nutrient requirements of several cultured freshwater fish in Indonesia. Heating treatments improved in vitro trypsin activity (1300 units/O and 1135 units/A vs. 835 units) but reduced protein (29.05±1.96%/A and 31.73±1.52%/O vs. 35.17±0.38%) and moisture contents. Additionally, the O treatment met the standards for aquafeed protein content (27-45%) and potentially fulfilled the protein requirements for catfish (25-40%), Nile tilapia (30-35%), and Java barb (30-32%). Therefore, oven heating presents a viable candidate as an alternative plant-based aquafeed ingredient. Nevertheless, the in vivo application of winged-bean meal as an aquafeed ingredient should be further evaluated to determine whether heating treatment effectively enhances digestive activity, nutrient retention, and growth performance in target fish species.